Strategi Pengembangan Kegiatan Ekonomi Kreatif PKK di Kota Tabanan terhadap Peningkatan Pendapatan Anggota - Dananjaya, I Gusti Agung Nyoman; Suparyana, Pande Komang; Setiawan, I Made Dedy; Yuniti, I Gusti Ayu Diah (Department of Agribusiness, Halu Oleo University, 2020)
The female workforce has productivity that plays a role and has the potential to support increased household income in rural areas. To provide guidance for women's productivity, a forum in the form of a PKK is needed that can be used by women. The purpose of this study was to identify the internal and external conditions of the PKK, as well as to determine the strategies that the PKK could use in Tabanan City in developing creative economic activities to increase member income. This research was conducted in Tabanan Regency at the PKK of each Village which was carried out from April to August 2020. Respondents consisted of 36 respondents from the PKK and 12 respondents from Kelian Dinas Banjar from the PKK. This research is a descriptive study that uses a strategic management approach, combining SWOT and AHP analysis for the best strategic decision making. The results of the research obtained are internal conditions in the development of PKK creative economic activities in Tabanan City, where the main strength factor is a solid group institution. The main weakness factors are lack of information on getting training activities and limitations in obtaining capital. Furthermore, external conditions in the development of PKK creative economic activities in Tabanan City, where the opportunity factor is good, namely the PKK group has a good image in the village government. For a major threat factor, namely the ease of duplicating products by competitors. So that we get the best strategy that can be applied in the development of PKK creative economic activities in Tabanan City, namely increasing the workforce of distributors to increase sales, in which product marketing requires product affordability to be well accepted by consumers.